KETERBUKAAN DIRI (SELF DISCLOSURE) PENCARI JODOH DALAM MENEMUKAN PASANGAN HIDUP MELALUI APLIKASI KENCAN DARING TINDER - Monica Catellya; Fitria Ayuningtyas; Dian Tri Hapsari (Institute of Research and Community Outreach - Petra Christian University, 2022)
Currently, Tinder is in great demand because it is proven by the presence of several couples who have made it to the stage of marriage. Factors of tension, anxiety, anxiety, shyness to an unattractive appearance make a person reluctant to do self-disclosure when having a face-to-face relationship. This research aims to find out how the motives, experiences, and meaning of self disclosure of mate seekers in finding a life partner through the Tinder application. This research uses a qualitative method with phenomenological approach. The theory in this research was the self-disclosure theory. Data collection techniques in this research were observation, and interviews. This research succeeded in revealing the motives of the informants to open themselves with their Tinder partners, namely to know more deeply and adapt to their Tinder partners. The experience of self-disclosure with a Tinder partner resulted in a positive and enjoyable experience because they could get to know their Tinder partner better. Interpreting self-disclosure as life as it is without lying to each other and a bridge between two different heads